Cellulose Functionalization via ATRP Grafting of Glycidyl Methacrylate for Cr(VI) Adsorption. Issue 12 (14th November 2013) - Lin, Chunxiang; Qiao, Sha; Liu, Danhui; Liu, Minghua
Abstract Cellulose was first grafted with glycidyl methacrylate (GMA) in an ionic liquid via atom transfer radical polymerization (ATRP) and then the introduced epoxy groups were reacted with ethanediamine (EDA) to obtain an amino adsorbent. The grafting copolymer and the obtained adsorbent were characterized by FTIR, 1H NMR, TEM and SEM. The results showed that the grafted copolymers had grafted polymer chains with well‐controlled molecular weight and polydispersity, the polymerization was a controlled system. The cellulose adsorbent had numerous micropores on the surface and showed high performance for Cr(VI) adsorption. The adsorption behavior was pH dependent and the sorption equilibrium was achieved within 2 h on the adsorbent.